Recent use of AB mix nutrients for urban farming in Malaysia: a mini review - Sanusi, Nur Dinie Syahirah; Ros, Fadhlina Che; Demon, Siti Zulaikha Ngah; Ismail, Ismayadi; Hamadneh, Imad (Penerbit Akademia Baru, 2024)
The use of AB mix nutrients in Malaysia is extensive especially in urban farming due to its all-inclusive-type of fertilizers. It possesses the advantage of providing a quick and high yield of agricultural products, along with a rapid response to signs of nutrient deficiency in plants due to the readily available nutrient-rich salts. However, extensive use of fertilizers led to significant environmental pollution in addition to the increase in agricultural productivity that we have today. Despite the fact that the Department of Agriculture Malaysia has published rules and suggested doses for using AB mix nutrients depending on the types of crops, farmers frequently over-fertilize their crops. Therefore, a survey has been carried out on several local agriculture entrepreneurs to compare their usage of AB mix nutrients for chili plants and the results revealed that majority of the respondents comply with the established guidelines. Sensible used of fertilizers must be promote amongst the farmers since intensive use of fertilizers will result to nutrient leaching into the soil, which contribute to environmental pollution, subsequently affecting the humans, livestock and microbial forms of life via food chain. In general, the impacts of the overuse chemical fertilizers are discussed from the aspects of plants physiology, quality of production and environment. The prospect of bio-fertilizer as a potential substitute to AB mix nutrients is also discussed. The increasing adoption of AB mix nutrients aligns with the demand for efficient urban farming methods, but it also brings into focus the critical balance between maximizing crop yield and minimizing ecological damage. This review emphasizes the significance of controlled nutrient application to prevent long-term soil degradation and groundwater contamination. Insights from comparative studies on fertigation and alternative fertilization methods, such as bio-fertilizers, provide a pathway toward more sustainable agricultural practices. The integration of bio-fertilizers into fertigation systems has shown promise in reducing reliance on chemical inputs, improving soil health, and supporting the sustainable intensification of urban agriculture. The paper also addresses the need for improved regulatory frameworks and awareness campaigns to mitigate the negative impacts of chemical fertilizer overuse and to promote organic alternatives in urban farming setups.